Decolonising African higher education practitioner perspectives from across the continent - Knaus, Christopher B.; Mino, Takako; Seroto, Johannes (Routledge, Taylor & Francis Group, 2022)
"This book clarifies decolonial efforts to transform higher education from its anti-Black foundation, offering hope from universities across the continent. Writers are university administrators and faculty who directly challenge contemporary colonial education, exploring tangible ways to decolonise structures, curricula, pedagogy, research, and community relationships. In shifting from a Western-centric lens to multi-faceted African-centrism, the authors reclaim decoloniality from co-optation, repositioning African intellectualism at the core of global higher education to sustain an Ubuntu-based humanity"--
Keywords: Education, Higher / Social aspects / Africa; Educational change / Africa; Postcolonialism / Africa; Afrocentrism; Enseignement supérieur / Aspect social / Afrique; Enseignement / Réforme / Afrique; Postcolonialisme / Afrique; Afro-centrisme; Education, Higher / Social aspects; Educational change; Postcolonialism; Africa